PERCEIVED QUALITY AND WILLINGNESS TO BUY AS DETERMINANTS OF PRICE CHANGE FREQUENCY: EVIDENCE FROM RETAIL STORES IN BANDUNG - Aziz, Aghni Aulia; Mufida Pertiwi, Ninda Annisa; Zaky, Muhammad (Journal of Management and Islamic Finance, 2025)
This study examines the influence of perceived quality and willingness to buy on the frequency of price change in the retail sector, using evidence from retail stores in Bandung, Indonesia. In highly competitive retail markets, price adjustments are often treated as firm-driven decisions; however, consumer perceptions and behavioral responses may also play a critical role in shaping pricing dynamics. Using a quantitative approach, data were collected from retail consumers and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that perceived quality has a positive and significant effect on the frequency of price change, suggesting that retailers tend to adjust prices more frequently when consumers perceive product quality favorably. In addition, willingness to buy is found to positively influence price change frequency, implying that stronger consumer purchase intention encourages retailers to respond more actively through pricing adjustments. These findings demonstrate that price change frequency in retail settings is not solely driven by internal cost or competitive factors but is also influenced by consumer evaluations and market signals. As a contribution to the literature, this study offers a novel perspective by positioning price change frequency as an outcome of consumer psychological constructs rather than merely a determinant of consumer behavior. The results provide practical insights for retail managers in Bandung and similar urban markets to design pricing strategies that are responsive to consumer perceptions while maintaining strategic pricing consistency.